Protective effect of single‐dose adjuvanted pandemic influenza vaccine in children - Van Buynder, P. G. (Influenza Other Respir Viruses, 2010)
Please cite this paper as: Van Buynder et al. (2010) Protective effect of single‐dose adjuvanted pandemic influenza vaccine in children. Influenza and Other Respiratory Viruses 4(4), 171–178. Background  During the first wave of A/California/7/2009(H1N1) influenza, high rates of hospitalization in children under 5 years were seen in many countries. Subsequent policies for vaccinating children varied in both type of vaccine and number of doses. In Canada, children 36 months to <10 years received a single dose of 0·25 ml of the GSK adjuvanted vaccine (Arepanrix™) equivalent to 1·9 μg HA. Children 6 months to 35 months received two doses as did those 36–119 months with chronic medical conditions. Method  We conducted a community‐based case–control vaccine effectiveness (VE) review of children under 10 years with influenza like illness who were tested for H1N1 infection at the central provincial laboratory. Laboratory‐confirmed influenza was the primary outcome, and vaccination status the primary exposure to assess VE after a single 0·25‐ml dose. Results  If vaccination was designated to be effective after 14 days, no vaccinated child had laboratory‐confirmed influenza compared to 38% of controls. The VE of 100% was statistically significant for children <10 years of age and <5 years considered separately. If vaccination was considered effective after 10 days, VE dropped to 96% overall but was statistically significant and over 90% in all age subgroups, including those under 36 months. Conclusions  A single 0·25‐ml dose of the GSK adjuvanted vaccine (Arepanrix™) protects children against laboratory‐confirmed pandemic influenza potentially avoiding any increased reactogenicity associated with second doses. Adjuvanted vaccines offer hope for improved seasonal vaccines in the future.